Mechanism of reduction of newborn metabolic acidemia following application of a rule-based 5-category color-coded fetal heart rate management framework. (29th September 2014) - Katsuragi, Shinji; Parer, Julian T.; Noda, Shunichi; Onishi, Junji; Kikuchi, Hitomi; Ikeda, Tomoaki
Abstracts: Objective: We have reported a 7-fold reduction in newborn umbilical arterial (UA) metabolic acidemia after adoption of a rule-based 5-category color-coded fetal heart rate (FHR) management framework. We sought evidence for the relationship being causal by detailed analysis of FHR characteristics and acid–base status before and after training. Methods: Rates of UA pH and base excess (BE) were determined over a 5-year period in a single Japanese hospital, serving mainly low-risk patients, with 3907 deliveries. We compared results in the 2 years before and after a 6-month training period in the FHR management system. We used a previously published classification schema, which was linked to management guidelines. Results : After the training period, there was an increase in the percentage of normal patterns (23%), and a decrease in variable decelerations (14%), late decelerations (8%) and prolonged decelerations (12%) in the last 60 min of labor compared to the pre-training period. There was also a significant reduction in mean UA pH and BE in the groups with decelerations after introduction of the FHR management framework. Conclusions: The adoption of this FHR management system was associated with a reduction of decelerations and metabolic acidemia, without a change in cesarean or vacuum delivery rates. These results suggest that the obstetrical providers were able to better select for intervention those patients destined to develop more severe acidemia, demonstrating a possible causal relationship between the management system and reduced decelerations and metabolic acidemia.